221. Save the Quinolones! Impact of a Non-Restrictive Fluoroquinolone Reduction Initiative on Antibiotic Resistance at an Urban Teaching Hospital. (26th November 2018) - Smoke, Steven; Plotkin, Slava; Patel, Neeki; Grigoriu, Adriana; DeVivo, Maria
Abstract: Background: The use of fluoroquinolones, one of the most commonly used antibiotic classes in the United States, is associated with adverse drug events, Clostridium difficile infection and antibiotic resistance in Staphylococcus aureus and other Gram-negative bacilli. Many hospitals have instituted resource-intensive interventions to minimize fluoroquinolone use. In hospital settings with fewer resources, education and awareness campaigns offer a more feasible approach. The purpose of this study was to assess the impact of a nonrestrictive fluoroquinolone reduction initiative on institutional antibiotic resistance. Methods: This is a retrospective pre- and postinterventional ecological study. The fluoroquinolone reduction initiative consisted of house staff education on risks of fluoroquinolone use and alternatives. Buttons promoting "Save the Quinolones" were also distributed and worn to increase visibility. The preintervention period and postintervention periods were February 2016 to December 2016 and February 2017 to December 2017, respectively. The primary outcome measure was the percentage of S. aureus susceptible to oxacillin isolated before and after the intervention. Secondary outcome measures were the rate of fluoroquinolone use, and the percentages of Escherichia coli, Proteus mirabilis, Klebsiella pneumoniae, and Pseudomonas aeruginosa susceptible to levofloxacin. Antibiotic use data were collected as inpatient intravenous antibiotic days of therapy per 1, 000 patient-days (DOT/1, 000 patient-days). Chi-square test was used to compare outcomes. Results: In the post intervention period, fluoroquinolone use decreased from 75 to 40.1 DOT/1, 000 patient-days (−34.9, 95% CI −37.3 to −32.5, P < 0.001). S. aureus susceptibility to oxacillin increased from 47.2% to 55.2% (difference 8.0, 95% CI 1.2 to 14.7, P = 0.02). P. aeruginosa susceptibility to levofloxacin increased from 60% to 70.7% (difference 10.7, 95% CI 0.8 to 20.6, P = 0.04). No difference in susceptibility rates of E. coli, P. mirabilis or K. pneumoniae was detected. Conclusion: A nonrestrictive fluoroquinolone reduction initiative led to a significant decrease in fluoroquinolone use. This was associated with decreased antibiotic resistance in S. aureus and P. aeruginosa . Disclosures: All authors: No reported disclosures.